Faktor – Faktor Yang Mempengaruhi Kualitas Laba Pada Perusahaan Manufaktur Di Bursa Efek Indonesia Pada Tahun 2019 - 2021 - Pramananta, Gede Adis; Wulandari, Putu Prima (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2024)
This study aims to empirically examine the factors that influence the quality of earnings in manufacturing companies on the Indonesia Stock Exchange (IDX) in 2019 – 2021. Earnings Response Coefficient (ERC) is measured. The factors studied are leverage, profitability, and liquidity in industrial manufacturing companies listed on the IDX in 2019 – 2021. There were 51 companies taken, company data that could be processed were 30 companies for 3 periods, namely 90 samples. The sampling method uses purposive sampling, while the testing technique used is linear regression analysis and uses the SPSS program. The test results show that the leverage variable has a significant negative effect on earnings quality. Then the profitability variable has a positive effect on earnings quality. Meanwhile, the liquidity variable has no significant negative effect on earnings quality.